Alkaline phosphatase protects against renal inflammation through dephosphorylation of lipopolysaccharide and adenosine triphosphate - Peters, Els; Geraci, Stefania; Kränzlin, Bettina; Gretz, Norbert; Masereeuw, R (British journal of pharmacology, 2015)
Background and Purpose Recently, two phase?II trials demonstrated improved renal function in critically ill patients with sepsis?associated acute kidney injury treated with the enzyme alkaline phosphatase. Here, we elucidated the dual active effect on renal protection of alkaline phosphatase. Experimental Approach The effect of human recombinant alkaline phosphatase (recAP) on LPS?induced renal injury was studied in Sprague?Dawley rats. Renal function was assessed by transcutaneous measurement of FITC?sinistrin elimination in freely moving, awake rats. The mechanism of action of recAP was further investigated in vitro using conditionally immortalized human proximal tubular epithelial cells (ciPTEC). Key Results In vivo, LPS administration significantly prolonged FITC?sinistrin half?life and increased fractional urea excretion, which was prevented by recAP co?administration. Moreover, recAP prevented LPS?induced increase in proximal tubule injury marker, kidney injury molecule?1 expression and excretion. In vitro, LPS?induced production of TNF?α, IL?6 and IL?8 was significantly attenuated by recAP. This effect was linked to dephosphorylation, as enzymatically inactive recAP had no effect on LPS?induced cytokine production. RecAP?mediated protection resulted in increased adenosine levels through dephosphorylation of LPS?induced extracellular ADP and ATP. Also, recAP attenuated LPS?induced increased expression of adenosine A2A receptor. However, the A2A receptor antagonist ZM?241385 did not diminish the effects of recAP. Conclusions and Implications These results indicate that the ability of recAP to reduce renal inflammation may account for the beneficial effect observed in septic acute kidney injury patients, and that dephosphorylation of ATP and LPS are responsible for this protective effect.
Gesehen am 21.03.2018